Cérémonies monarchiques et musique à la cour de Charles Quint - Louise Audubert (E-Spania)
The modern period sees developing and enriching the protocol surrounding the ceremonies of a monarch’s reign. The choice of a study dedicated to Charles V (1500-1558) is understandable not only by his exceptional destiny as the first Habsburg on the throne of Spain, but also by the new place devolved to the music in his Court. The facts of the life of the Emperor and his family – marriage, birth and death –, as well as the crowning and events around the Order the Golden Fleece, are many occasions of luxurious ceremonies where the music occupies a special place. Chronicles and iconographies of the time often give only very summary indications of the musical contents of these various rites of the monarchy. But some musicologists’ works on the circumstance anthems of the first half of the XVIth century allow to raise the significant role that could play the music in the celebration of the power in Charles V’s Court.